Workers' struggle at the Iloilo Waterfront in the late 1990s the case of the workers of the F.F. Marine Corporation. - Tingson, Mary Genevieve Fanega
This is a case study of the effects of the globalization on the workers of the F.F. Marine Corporation, shipbuilding and ship repair division of the F.F. Cruz and Company, Inc. located in Iloilo. The study tackles both the economic and political effects of globalization on the workers of the said company in the latter half of the 1990s., The objective of the study is to determine, as a whole, how globalization, which is manifested in the liberalization, deregulation and privatization of the Philippine economy, affect the workers on the study. The study aims to identify and characterize globalization and relate it to the contemporary labor situations in the third world. Secondly it tries to determine the political and economic situations in the F.F. Marine Corporation that were affected by the present global conditions. thirdly, it seeks to discuss the struggle of the workers' union in the said company as the eventual effect of globalization. Lastly, it tries to explain and analyze the political struggle of the said workers' union Dry-docking Employees Association (IDEAS), in the context of globalization. The study focuses on the struggle of the workers of the F.F. Marine Corporation. Different respondents from the union, members and/or organizers, including the management, if possible, will be interviewed. Workers' struggle at the Iloilo waterfront is no different. It has been known to have existed since the 1920s where workers, the bulk of which were composed of stevedores, struggled against retrenchments and unfair labor practices of several companies in the shipping industry. The worsening economic crisis brought about by globalization has tremendous effects on the working class. Globalization has not done away with exploitation of the workers in the Iloilo waterfront, despite their tactical gains, since the 1920s. In fact it further intensified and worsened the exploitation of the workers. Exploitation and oppression forced the workers to unite and organize a labor union to protect and advance their class interest. Whereas before, the demand and struggle of the worker and their labor unions were purely economic, today, however, it takes a new form. Workers' struggle today is not only economic in nature, but also,political. It extends and integrates with the struggle of the broad masses of the people in an effort to end exploitation as a whole.